INOVASI PRODUK AGROINDUSTRI DARI PERSPEKTIF ANALISIS FUNGSIONAL CONTOH KASUS: TELUR ASIN ANEKA RASA - Zulfiandri Zulfiandri; M. Syamsul Maarif; Yandra Arkeman (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
Agroindustry is important industry which necessary for economics of Indonesia.Many local products from agroindustry was developed by people initially as analternative for survival on. One of the product of local agroindustryknown long timewhich is developed by people are salty egg. Egg from duck is salted. Salty egg is one ofthe example how a product of agroindustry developed by entrepreneur of people andsmall scale business. By using functional analysis, which develop product pursuant tointrinsic function value of itself. Salty egg as one of the product of agroindustri can beaccepted by wider market that is conducted by product innovation. As examplesaremultivarious salty egg variant taste.